Eating Hubs in Multiple Sclerosis: Exploring the Relationship Between Mediterranean Diet and Disability Status in Italy - Felicetti, Federica; Tommasin, Silvia; Petracca, Maria; De Giglio, Laura; Gurreri, Flavia; Ianniello, Antonio; Nistri, Riccardo; Pozzilli, Carlo; Ruggieri, Serena (Frontiers in Nutrition, 2022)
Background. Multiple Sclerosis (MS) is a complex disease in which multiple factors contribute to disability accrual. Mediterranean Diet (MeDi) has shown beneficial effects across neurodegenerative diseases. We hypothesize that specific food habits, rather than global adherence to MeDi, might impact on MS. We aimed to (i) evaluate differences in adherence to MeDi between people living with MS (PwMS) and healthy controls (HC); (ii) characterize eating patterns in PwMS and HC, identifying the most influential MeDi items for each group by the use of network analysis; (iii) explore the relationship between patients’ eating habits and disability. Materials and Methods. In this cross-sectional study, we consecutively recruited 424 PwMS and 165 matched HC. Data were obtained through the administration of self-reported questionnaires. Expanded Disability Status Scale (EDSS) and Fatigue Severity Scale (FSS) were evaluated in the MS population. We performed between-groups comparisons via unpaired two-sample t test and X2 test as appropriate. We calculated food networks in both MS cases and HC using and tested the association between hub nodes and disability. Finally, we conducted a post-hoc analysis, investigating the relationship between food items, lifestyle factors (smoking, exercise) and clinical outcomes. Results: Most participants adhered sufficiently to MeDi. Exploring each group separately, fruit, vegetables, cereal and fish were identified as hubs in PwMS, while meat and alcohol were identified as hubs in HC. Hubs were all inter-correlated, indicating that eating habits of PwMS include a large intake of all the foods identified as hubs. EDSS was predicted by the intake of vegetables (beta=-0.36, p<0.03) and fish (beta=-0.34, p<0.02). The model including smoking pack/year, International Physical Activity Questionnaire (IPAQ) score and intake of “negative foods” predicted 6% of the variance in EDSS (p<0.001), while the model including smoking pack/year and IPAQ score predicted 4% of the variance in FSS (p<0.001). Conclusions. We identified a sufficient adherence to MeDi in our population. PwMS showed overall a healthier dietary pattern than HC. Vegetables and fish intake were associated with disability outcomes. Future longitudinal studies applying integrated approaches are needed to understand lifestyle added value to the use of standard pharmacological therapies.